Kemiskinan Masyarakat Urban Makassar - Ananda Umar, Devia; Sam’un Mukramin; Jamaluddin Arifin; Fatimah Aziz (Jurnal Kajian dan Penelitian Umum, 2023)
Poverty is described as the inability to meet basic needs due to lack of income, making it increasingly difficult to guarantee survival (Suryawati, 2004). When a country's poverty rate is high, the purchasing power of its citizens decreases which has a negative impact on economic growth (Fajri & Iriani, 2022). This study aims to determine the effect of economic growth on the poverty rate in Makassar City, and to determine the effect of unemployment on the poverty rate in Makassar City by using primary data and secondary data, data collection techniques, literature studies and interviews, and then analyzed qualitatively (Ishak et al. , 2020). The results of the study show that the inability to access education and health and proper employment has subsequently had an impact on increasing the number of unemployed in the workforce. In other words, poverty can have an impact on unemployment and a lack of income, and then unemployment itself creates a poor community